Russula buyckii, a new species of Russula subgenus Incrustatula from Eastern Himalaya, India - Paloi, Soumitra; Dutta, Arun Kumar; Pradhan, Prakash; Roy, Anirban; Acharya, Krishnendu (Phytotaxa, 2016)
Russula buyckii, a new species of Russula (subgen. Incrustatula, sect. Lilaceinae and subsect. Lilaceinae) is described from Eastern Himalaya, India. Its macro- and micro-morphological features are described in detail and compared with those of similar species. Identification and categorization of R. buyckii was supported by the molecular phylogenetic analysis based on the nrDNA ITS sequence data.